Pengaruh Kinerja Ekuitas Merek terhadap Proses Keputusan Pembelian Konsumen Minuman Isotonik Mizone pada Pelanggan Hypermart MATOS Malang - Yuan, Yamunna; By, Djasly (Universitas Brawijaya, Indonesia, 2008)
Isotonic drink is a kind of ionic drink and it changes the body liquid that have been lost. Nowadays, the competition in isotonic drink industries is getting higher. It can be seen from the variety kinds of isotonic drink which are predicted to be growing. Mizone is one of this isoionic drink which is produced by PT. Danone Aqua. The consumer's choice for Mizone or the competitor is based on his judgment about that product's brand. The value of brand can be seen by its brand equity which is formed by various judgment, such as measuring brand awareness, brand loyalty perceived quality, and brand association High brand equity would give the customer's belief to choose the products brand. The aim of this research is to know about the performance of Mizone's brand equity and trace the customer's buying decision process in Hypermart MATOS Malang. Besides, to analyze the influence of performance on Mizone's brand equity toward the customers buying decision process in Hypermart MATOS Malang. This research is a kind of survey which is purposed for confirmatory or explanatory research, it means that explains the causal relationship among variables through hypothesis tested. The result of this research shows that variables of brand equity, such as Brand Awareness, Brand Loyalty, Perceived Quality, and Brand Association influence the customer's buying decision process of Mizone either directly or indirectly. The total effect is 68,5%, with brand loyalty us the biggest influence.